Anaphylaxis: guidelines from the European Academy of Allergy and Clinical Immunology. Issue 8 (9th June 2014) - Muraro, A.; Roberts, G.; Worm, M.; Bilò, M. B.; Brockow, K.; Fernández Rivas, M.; Santos, A. F.; Zolkipli, Z. Q.; Bellou, A.; Beyer, K.; Bindslev‐Jensen, C.; Cardona, V.; et al.
Abstract Anaphylaxis is a clinical emergency, and all healthcare professionals should be familiar with its recognition and acute and ongoing management. These guidelines have been prepared by the European Academy of Allergy and Clinical Immunology (EAACI) Taskforce on Anaphylaxis. They aim to provide evidence‐based recommendations for the recognition, risk factor assessment, and the management of patients who are at risk of, are experiencing, or have experienced anaphylaxis. While the primary audience is allergists, these guidelines are also relevant to all other healthcare professionals. The development of these guidelines has been underpinned by two systematic reviews of the literature, both on the epidemiology and on clinical management of anaphylaxis. Anaphylaxis is a potentially life‐threatening condition whose clinical diagnosis is based on recognition of a constellation of presenting features. First‐line treatment for anaphylaxis is intramuscular adrenaline. Useful second‐line interventions may include removing the trigger where possible, calling for help, correct positioning of the patient, high‐flow oxygen, intravenous fluids, inhaled short‐acting bronchodilators, and nebulized adrenaline. Discharge arrangements should involve an assessment of the risk of further reactions, a management plan with an anaphylaxis emergency action plan, and, where appropriate, prescribing an adrenaline auto‐injector. If an adrenaline auto‐injector is prescribed, education on when and how to use the device should be provided. Specialist follow‐up is essential to investigate possible triggers, to perform a comprehensive risk assessment, and to prevent future episodes by developing personalized risk reduction strategies including, where possible, commencing allergen immunotherapy. Training for the patient and all caregivers is essential. There are still many gaps in the evidence base for anaphylaxis.